2022
DOI: 10.1111/are.15892
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, physiological and antioxidant capacity responses to dietary fish meal replacement with insect meals for aquaculture: A case study in red claw crayfish ( Cherax quadricarinatus )

Abstract: A 60‐day feeding trial was conducted to evaluate the effects of yellow mealworm (YM) (Tenebrio molitor) (9%, 18%, 27% and 36%) and black soldier fly larvae (BSFL) (Hermetia illucens) (7%, 14%, 21% and 28%) meal replacing fish meal (FM) on growth performance and antioxidant capacity of red claw crayfish (Cherax quadricarinatus). Nine diets, including control, were fed with quadruplicate of 20 crayfish (0.20 ± 0.05 g). The highest weight gain (WG) and lowest feed conversion ratio were observed in crayfish fed YM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Concerning the effects of HM in the diet of other crustacean and fish species, Wang et al (2022) proposed that the optimum inclusion of HM in the diet of C. quadricarinatus , was 17.1%, probably implying that for better growth performance the substitution level with HM should be lower than 50%. Additionally, growth performance of juvenile Pacific white shrimp L. vannamei was similar to the control group when the fishmeal replacement with HM was restricted to less than 25% ( Cummins et al, 2017 ) and decreased significantly with a 30% replacement ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the effects of HM in the diet of other crustacean and fish species, Wang et al (2022) proposed that the optimum inclusion of HM in the diet of C. quadricarinatus , was 17.1%, probably implying that for better growth performance the substitution level with HM should be lower than 50%. Additionally, growth performance of juvenile Pacific white shrimp L. vannamei was similar to the control group when the fishmeal replacement with HM was restricted to less than 25% ( Cummins et al, 2017 ) and decreased significantly with a 30% replacement ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published studies using H. illucen s meal for fishmeal replacement have been conducted majorly in farmed fish species such as rainbow trout ( Stadtlander et al, 2017 ), Atlantic salmon ( Li et al, 2020 ), European sea bass ( Magalhães et al, 2017 ), gilthead seabream ( Karapanagiotidis et al, 2023 ), African catfish ( Fawole et al, 2020 ), Nile tilapia ( Tippayadara et al, 2021 ) and yellow catfish ( Xiao et al, 2018 ), and only few in crustaceans such as pacific white shrimp ( Cummins et al, 2017 ) and red claw crayfish ( Wang et al, 2022 ). For P. leptodactylus , Mazlum et al (2021) evaluated the use of Tenebrio molitor and reported that a dietary inclusion level of 13.5%, representing 50% of fishmeal replacement, was successful in terms of growth performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even 1% H. illucens meal significantly improved the palatability of the compound feed (Terrey et al, 2021). Positive effects on crustaceans such as the Longarm river prawn (Macrobrachium tenellum), Danube crayfish (Pontastacus leptodactylus), Smooth marron (Cherax cainii), Australian red claw crayfish (Cherax quadricarinatus) and M. rosenbergii were also observed when they were fed on insects, including other species such as Trichocorixa sp., M. domestica, B. mori, Two-spotted cricket (Gryllus bimaculatus), Japanese rhinoceros beetle (Allomyrina dichotoma), Short-horned grasshopper (Oxya chinensis) and Protaetia brevitarsis (De León-Ramírez et al, 2018;Foysal et al, 2019Foysal et al, , 2021Martínez-Córdova et al, 2013;Mazlum et al, 2021;McCallum et al, 2021;Peh et al, 2021;Shin and Lee, 2021;Wang et al, 2022) (Table S1, Figure 3). Although the precise mechanisms have not been identified in crustaceans, there is ample evidence that insect supplements confer growth and health benefits (Table S1).…”
Section: Insect-based Crustacean Feedmentioning
confidence: 99%
“…Dietary protein directly affects healthy growth, feed intake, and feed costs in aquaculture and is the most expensive nutrient in the diet (Sivaramakrishnan et al, 2022). Fishmeal is the primary source of protein in aquaculture feed and has high percentages in aquaculture formulations (Wang et al, 2022). This is as a result of its high protein content, balanced amino acid composition, and fatty acid profile (Tacon & Metian, 2015).…”
Section: Introductionmentioning
confidence: 99%